Regional anaesthesia : a pocket guide - Chuan, Alwin; Scott, David Michael ([Oxford] : Oxford University Press, 2014)
A quick-reference pocketbook for trainees and consultants working in regional anaesthesia. Step-by-step guidelines for essential procedures are accompanied by quality clinical photographs and diagrams covering the four core areas of the specialty.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 31, 2014).
Keywords: Conduction anesthesia; Conduction anesthesia -- Pictorial works